2020
DOI: 10.1007/s12103-020-09578-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Immediate Effects of COVID-19 Containment Policies on Crime: an Empirical Analysis of the Short-Term Aftermath in Los Angeles

Abstract: This work investigates whether and how COVID-19 containment policies had an immediate impact on crime trends in Los Angeles. The analysis is conducted using Bayesian structural time-series and focuses on nine crime categories and on the overall crime count, daily monitored from January 1st 2017 to March 28th 2020. We concentrate on two post-intervention time windows—from March 4th to March 16th and from March 4th to March 28th 2020—to dynamically assess the short-term effects of mild and strict policies. In Lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(164 citation statements)
references
References 56 publications
7
143
3
2
Order By: Relevance
“…Abrams (2020) found no significant increase in homicides and shootings during the pandemic across 25 large cities in the United States. In addition, no significant change was detected for homicides and assaults with a deadly weapon in Los Angeles ( Campedelli et al, 2020 ). At the international level, the effects of the pandemic on homicides differed by country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abrams (2020) found no significant increase in homicides and shootings during the pandemic across 25 large cities in the United States. In addition, no significant change was detected for homicides and assaults with a deadly weapon in Los Angeles ( Campedelli et al, 2020 ). At the international level, the effects of the pandemic on homicides differed by country.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no decrease in murders and shootings. Campedelli et al (2020) , using daily crime data from 2017 to March 2020 in Los Angeles, found evidence of decreases in robbery, shoplifting, theft, and battery. No significant changes were found for vehicle theft, burglary, assault with a deadly weapon, intimate partner assault, and homicide.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One consequence of the COVID-19 health crisis has been the proliferation of studies related to clinical research to generate methods for the disease's treatment including the contextual and psychological effects derived from the pandemic. In this sense, we must determine the consequences of the pandemic on other levels [33][34][35][36], including the emotional and psychological levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, as Payne et al (2020) pointed out, their studies were limited to a short-term analysis and unable to disentangle seasonal trends and more longer-term crime patterns. Thus, Campedelli et al (2020) analysed reported crime data from 1 January 2017 and 28 March 2020 in Los Angeles to investigate the impact on crime trends. They used Bayesian structural time-series models and found that overall crime, robbery, shoplifting, theft, and battery had significantly decreased, but no significant effect on vehicle theft, burglary, assault with a deadly weapon, intimate partner assault, and homicide.…”
Section: Previous Studiesmentioning
confidence: 99%